Left ventricular rupture postradiofrequency catheter ablation: Transaortic, intraventricular patch exclusion repair. Issue 6 (1st February 2021) - Verdichizzo, Danilo; Gill, Jaswinder; Krasopoulos, George
Abstract: Left ventricular (LV) rupture after radiofrequency catheter ablation (RFCA) is a rare but life‐threatening complication. We describe a case of LV rupture secondary to RFCA successfully treated with a transaortic, intraventricular patch exclusion surgical repair, assisted by transoesophageal echocardiography and epicardial ultrasound assessment. Patch exclusion technique can offer a physiological repair with better preservation of myocardial mechanical characteristics and possibly less damage to healthy myocardium and surrounding structures.